"Anti-theft security alarm" apps blueprint / Nurul Syuhada R. Azmi, Intan Zahida Ahmad Mustaza and Nurul Asyikin Ab Wahab - R. Azmi, Nurul Syuhada; Ahmad Mustaza, Intan Zahida; Ab Wahab, Nurul Asyikin (2018)
The product the group has chosen is Anti-Theft Security Alarm. This product can secure the motorcycle from stolen by monitor any movement that was made by the thief. This product is applicable to any size of motorcycle.